HUBUNGAN LOKASI DAN PROMOSI DENGAN KEPUTUSAN PEMBELIAN RUMAH SUBSIDI PADA PT. GRAHA ESTETIKA PROPERTY BENGKULU - Sri Handayani; Miko Warodei Antono (Management Insight: Jurnal Ilmiah Manajemen, 2018)
The purpose of this study was to determine the relationship between location and the decision to purchase a subsidy at PT. Graha Estetika Property Bengkulu and to find out the relationship of promotion with the decision to purchase a subsidized house at PT. Graha Estetika Property Bengkulu. The method of analysis uses Spearman rank correlation and hypothesis testing. Spearman rank correlation coefficient on location relationship (X1) with subsidized house purchase decision (Y) at PT. The Bengkel Property Aesthetic Graha is known that the value of rho count = 0.85 means the relationship between the location and the decision to purchase a subsidy at PT. Bengkulu's Graha Estetika Property is very strong, because the correlation value is in the coefficient interval of 0.800 - 1,000. The value of the Spearman rank correlation coefficient on the relationship of promotion (X2) with the decision to purchase a subsidized house (Y) at PT. Bengkel Property Aesthetic Graha is known the value of rho count = 0.68 the meaning of the promotion relationship with the purchase of a house subsidy decision at PT. Bengkulu's Graha Aesthetic Property is strong, because the correlation value is in the coefficient interval of 0.600 - 799.